Pelatihan Bahasa Inggris dan Digital Marketing dalam Rangka Peningkatan Pariwisata dan Ekonomi Kreatif Sumber Daya Nagari Unggan: Pengabdian - Nurul Inayah Hutasuhut; Agusti Efi; Reska Mayefis; Febri Silvia; Rizal Arifin Lubis; Violintikha Harmawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Nagari Unggan, located in Sijunjung Regency, is known as the "Weaving Village." The craft of weaving, predominantly undertaken by women, has become a specific economic opportunity for the community. However, several challenges hinder the recognition of Unggan's weaving craft. Although Unggan has tour guides, their ability to communicate effectively with foreign tourists is considered insufficient. This is significant because communication is a key factor in promoting the weaving craft. Additionally, the marketing of the weaving products remains suboptimal due to the distance and difficult access to areas outside Nagari.To address these issues, training programs focusing on enhancing English language proficiency and digital marketing skills for the residents of Nagari Unggan are proposed as solutions. These activities involve discussions, lectures, and hands-on field practices, including demonstrations on creating digital accounts and websites. The program follows a structured approach comprising preparation, implementation, and evaluation phases to ensure sustainability.The effectiveness of the program is evident from the participants' improved understanding before and after the training, with a significant difference indicated by a significance value of 0.00 for both training sessions. Strong commitment from the local government is expected to accelerate the growth of the creative economy in Unggan.